2020
DOI: 10.1371/journal.pone.0231599
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic disparities in colorectal cancer treatment utilization and phase-specific costs, 2000-2014

Abstract: Background Our study analyzed disparities in utilization and phase-specific costs of care among older colorectal cancer patients in the United States. We also estimated the phase-specific costs by cancer type, stage at diagnosis, and treatment modality. Methods We used the Surveillance, Epidemiology, and End Results (SEER)-Medicare database to identify patients aged 66 or older diagnosed with colon or rectal cancer between 2000-2013, with follow-up to death or December 31, 2014. We divided the patient's experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 61 publications
1
36
0
Order By: Relevance
“…Further, these differences persisted when comparing racial cohorts with the same health insurance status, suggesting that adequate insurance coverage is not associated with mitigated racial disparities in cancer care delivery. Across all stages of diagnosis, Black patients are less likely to receive treatment for colorectal cancer [15]. Prior studies of the Surveillance Epidemiology and End Results (SEER) registry have demonstrated that Black patients have lower odds of undergoing surgery for colorectal cancer [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, these differences persisted when comparing racial cohorts with the same health insurance status, suggesting that adequate insurance coverage is not associated with mitigated racial disparities in cancer care delivery. Across all stages of diagnosis, Black patients are less likely to receive treatment for colorectal cancer [15]. Prior studies of the Surveillance Epidemiology and End Results (SEER) registry have demonstrated that Black patients have lower odds of undergoing surgery for colorectal cancer [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Across all stages of diagnosis, Black patients are less likely to receive treatment for colorectal cancer [ 15 ]. Prior studies of the Surveillance Epidemiology and End Results (SEER) registry have demonstrated that Black patients have lower odds of undergoing surgery for colorectal cancer [ 15 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has shown that underutilization of medical resources in Black patients in the United States is a significant societal problem. 46 , 47 Further studies are needed to determine if explicit or implicit racism plays a role in this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, 18 studies were analyzed. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] The total number of patients included 89,214 black patients and 646,990 white patients, ranging from 513 to 11,111 and 2,047 to 190,688, respectively. In all articles, a retrospective analysis of patients was presented including the outcome of surgical utilization.…”
Section: Resultsmentioning
confidence: 99%